Progress in monitoring alcohol consumption and alcohol abuse by phosphatidylethanol. (September 2014) - Schröck, Alexandra; Thierauf, Annette; Wurst, Friedrich Martin; Thon, Natasha; Weinmann, Wolfgang
For early diagnosis and therapy of alcohol-related disorders, alcohol biomarkers are highly valuable. Concerning specificity, indirect markers can be influenced by nonethanol-related factors, whereas direct markers are only formed after ethanol consumption. Sensitivity of the direct markers depends on cut-offs of analytical methods, material for analysis and plays an important role for their utilization in different fields of application. Until recently, the biomarker phosphatidylethanol has been used to differentiate between social drinking and alcohol abuse. After method optimization, the detection limit could be lowered and phosphatidylethanol became sensitive enough to even detect the consumption of low amounts of alcohol. This perspective gives a summary of most common alcohol biomarkers and summarizes new developments for monitoring alcohol consumption habits.